2021
DOI: 10.1007/s00520-021-06238-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions around bone-modifying agent use in patients with bone metastases from breast and castration resistant prostate cancer: a patient survey

Abstract: Background Optimal use of bone-modifying agent (BMA) therapy in patients with bone metastases from breast and castrateresistant prostate cancer (CRPC) is evolving. Methods Patients receiving BMA for bone metastases from breast or CRPC were surveyed. Information was collected on patient and disease characteristics, BMA treatments and perceptions regarding BMA benefits and side effects. Interest in participation in trials of de-escalated BMA therapy was also gauged. Results Of 220 patients contacted, 172 eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The drug choice may depend on many criteria: direct and indirect costs, real or supposed risk of SREs or SSEs, risk of early disease progression and/or worsening of performance status or quality of life (QoL), comorbidities, risk of side effects, patient’s preferences, and life expectancy [ 10 , 16 , 17 , 19 , 20 , 23 25 , 27 , 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The drug choice may depend on many criteria: direct and indirect costs, real or supposed risk of SREs or SSEs, risk of early disease progression and/or worsening of performance status or quality of life (QoL), comorbidities, risk of side effects, patient’s preferences, and life expectancy [ 10 , 16 , 17 , 19 , 20 , 23 25 , 27 , 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Denosumab is a classic drug that targets the receptor activator of the NF-κβ ligand (RANKL) [57] . A retrospective study of 84 patients with MBCB found that most patients treated with denosumab benefited from fracture arrest, improved quality of life, and prolonged survival [58] . Others have mentioned that the use of denosumab is effective in reducing the probability of skeletal-related events, including disability and bone pain [52] , [53] .…”
Section: Discussionmentioning
confidence: 99%
“…All of these surveys involved patients with breast cancer. Two surveys included patients with bone metastases, evaluating the use of bone-modifying agents (BMAs) accrued patients with breast cancer and castration resistant prostate cancer (CRPC) [61,68].…”
Section: Patient Surveysmentioning
confidence: 99%
“…This occurred because of the increasing recognition that not all surveys required written consent and indeed the requirement for written consent could reduce the validity of study findings to reflect as broad a patient population as possible. Potential patients for surveys were often identified in the clinic (11/15), however in more recent surveys patients have also been identified and approached through their involvement in other studies [29,32] and pharmacy lists [50,68]. With the introduction of the MyChart function within the EPIC EMR patients are also now able to consent to being contacted about other studies [29,32].…”
Section: Patient Surveysmentioning
confidence: 99%
See 1 more Smart Citation